Sistem Informasi Akuntansi dan Pengendalian Internal pada Gudang Spare Part PT. Socfin Indonesia Perkebunan Aek Pamienke - Meisyah Rambe; Nurlaila Nurlaila (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
All companies, whether service companies, trading companies, or manufacturing companies require the presence of a good system and procedures to protect and support the smooth running of company activities. This study aims to see whether the accounting information system and internal control carried out by PT Socfin Indonesia Aek Pamienke Plantation have been running effectively. The author uses a descriptive qualitative approach by studying literature, collecting documents, and observing in the field. Researchers found that the accounting information system and internal control at the Spare Part Warehouse of PT Socfin Indonesia Aek Pamienke Plantation have been running effectively. The company has used an accounting information system in preparing warehouse reports and carrying out the SOPs that apply in the company.